Peningkatan Keterampilan Menyampaikan Arahan Teks Prosedur Dengan Metode Project Based Learning (Pjbl) Melalui Media Instagramreels - Amalia Firdausa; Sintowati Rini Utami; Yantia Elestisa Lumbantobing (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is a classroom action research with the aim of improving students' speaking skills using the Project Based Learning method through Instagram reels media. The subjects of this study were 35 class VII D students of SMP Negeri 7 Jakarta. This research was conducted for three cycles with the stages of each cycle as follows (1) planning, (2) implementation, (3) observation, and (4) reflection. The data collection technique used in this study was by using observation sheets for students' speaking skills activities and speaking skills tests. The results showed an increase in the average value of students' speaking. The average value obtained in cycle 1 with a percentage of 52.85% is in the "Pretty Good" category, cycle II reaches 76.67% which is in the "Good" category and in cycle III with a percentage of 87.92% in the "Very Good" category ”. There was a change in the average value of students' speaking skills when doing cycle III was due to changes in behavior such as students being enthusiastic, not embarrassed, not afraid, looking confident, and concentrating on the lesson. The results of the research that occurred on the increase in students' speaking class using Instagram reels media with the Project Based Learning method.